Teknik Brainstorming Dalam Bimbingan Kelompok Terhadap Perilaku Bullying - Purniawati; Astuti, Anita Dewi (Fakultas Dakwah dan Komunikasi, UIN Raden Fatah Palembang, 2024)
Bullying behavior is aggressive behavior that aims to hurt other people both physically and verbally. This research examines the effect of group guidance services using brainstorming techniques on the bullying behavior of class VIII students at SMP Negeri 3 Sentolo Kulon Progo. Using a quantitative experimental approach, this research involved 20 students selected by purposive sampling from a total population of 179 students. Data was collected through a questionnaire that had been tested for validity and reliability, and analyzed using the independent sample T test with the SPSS version 27.0.1 program. The results showed that the experimental group had a higher posttest score (132.20) than the control group (92.80), with a significance value of 0.000 < 0.05. Therefore, the working hypothesis which states that there is an influence of group guidance services using brainstorming techniques on the bullying behavior of class VIII students at SMP Negeri 3 Sentolo Kulon Progo for the 2024/2025 academic year is